Channel Characterization of a Dense UMTS and LTE Network for Improved Services in South-West, Nigeria - U, Nnebe Scholastica; Ochim, Odeh I (International Journal of Computer Sciences and Engineering, 2021)
The need for excellent delivery in wireless communication and the demand for high data rate transmission have resulted in the investigation of propagation mechanisms for higher-order frequencies, with enormous prospects in increasing data rate with respect to higher bandwidth. Deficiencies in the wireless channel such as poor signal quality, blocked calls, dropped calls, interference problems, etc make it eminent for the development of path loss prediction and estimation models that predict the signal strength of any given terrain. This research is focused on determining the mathematical model that characterizes the propagation environment of a dense urban area in Lagos, Nigeria (Festac town).